2011
DOI: 10.1002/pssa.201127172
|View full text |Cite
|
Sign up to set email alerts
|

Minicrystallization in directionally solidified multicrystalline silicon and its effect on the photovoltaic properties of solar cells

Abstract: In this paper, we report the occurrence of minicrystallization in multicrystalline silicon ingots grown by the directional solidification method and its effect on the photovoltaic (PV) properties of multicrystalline silicon solar cells. Minicrystallization in multicrystalline silicon ingots sometimes occurs when the directional solidification process is not properly optimized, and it causes much smaller grain sizes in the minicrystallized regions. Serious shunting behaviour has been observed in multicrystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In order to enhance the PV performance of mc-Si solar cells, a lot of effort has been devoted to reducing the number of grain boundaries and the dislocation densities in mc-Si [7,25,26]. However, the occurrence of minicrystallization [27] in mc-Si ingots that are grown by the directional solidification method introduces much smaller grains within the minicrystallized regions (Figure 1), resulting in a larger number of grain boundaries within these regions, which can degrade the PV performance of mc-Si solar cells. Up to now, little research has been reported on the dislocation characteristics in the minicrystallized regions in mc-Si ingots grown by the directional solidification method.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the PV performance of mc-Si solar cells, a lot of effort has been devoted to reducing the number of grain boundaries and the dislocation densities in mc-Si [7,25,26]. However, the occurrence of minicrystallization [27] in mc-Si ingots that are grown by the directional solidification method introduces much smaller grains within the minicrystallized regions (Figure 1), resulting in a larger number of grain boundaries within these regions, which can degrade the PV performance of mc-Si solar cells. Up to now, little research has been reported on the dislocation characteristics in the minicrystallized regions in mc-Si ingots grown by the directional solidification method.…”
Section: Introductionmentioning
confidence: 99%